Cadaver wrapping and attendance performance of adult flies in an oil palm plantation in northern Peninsular Malaysia - Azwani, Ahmad; Abu Hassan, Ahmad; Hamady, Dieng; Tomomotsu, Satho; Hamdan, Ahmad; Al Thbyani, Aziz; Micheal, Boots (Entomological Society of America, 2011)
There is accumulating evidence that criminals wrap dead bodies in an attempt to conceal evidence. To anticipate the forensic implications of this phenomenon, we examined whether ßies that are naturally associated with cadavers exhibit a delay in attendance or differ in species composition and abundance patterns because of the presence of wrapping material. Wrapped and exposed carcasses of dead monkeys placed in an oil plantation in Kedah, Malaysia, were visited over 50 d. On daily visits to each of the six carcasses, visiting adult ßies were sampled using hand nets. Flies of 12 families were encountered. Calliphoridae (Chrysomya rufifacies Macquart and C. megacephala (F.) was the most prevalent family, followed by Sphaeroceridae. Some families tended to be more abundant in WRCs (i.e., Calliphoridae, Muscidae, and Phoridae), whereas others (i.e., Piophilidae, Sepsidae, and Psychodidae) were more prevalent in exposed carcasses. Wrapping delayed the arrival of all ßy species encountered, with delays varying from 1 to 13 d depending on species. Wrapping did not affect species composition of ßies, but prolong the occurrence of some species. The results of the current study emphasize the need to take into consideration the presence of a wrap when estimating postmortem interval.